Molecular mechanisms of ferroptosis and relevance to inflammation - Deng, Liyan; He, Shasha; Guo, Nuoqing; Tian, Wen; Zhang, Weizhen; Luo, Lianxiang (Inflammation research, 2023)
Introduction Inflammation is a defensive response of the organism to irritation which is manifested by redness, swelling, heat, pain and dysfunction. The inflammatory response underlies the role of various diseases. Ferroptosis, a unique modality of cell death, driven by iron-dependent lipid peroxidation, is regulated by multifarious cellular metabolic pathways, including redox homeostasis, iron processing and metabolism of lipids, as well as various signaling pathways associated with diseases. A growing body of evidence suggests that ferroptosis is involved in inflammatory response, and targeting ferroptosis has great prospects in preventing and treating inflammatory diseases. Materials and methods Relevant literatures on ferroptosis, inflammation, inflammatory factors and inflammatory diseases published from January 1, 2010 to now were searched in PubMed database. Conclusion In this review, we summarize the regulatory mechanisms associated with ferroptosis, discuss the interaction between ferroptosis and inflammation, the role of mitochondria in inflammatory ferroptosis, and the role of targeting ferroptosis in inflammatory diseases. As more and more studies have confirmed the relationship between ferroptosis and inflammation in a wide range of organ damage and degeneration, drug induction and inhibition of ferroptosis has great potential in the treatment of immune and inflammatory diseases.